Assessment of the occurrence of phthalate esters (PAEs) in indoor office PM2.5 from Brazil and the UK - Cristian Ryan A. Argamino; Jéssica dos Santos Silva; Jishnu Pandamkulangara Kizhakkethil; Svetlana Stevanovic; Martyn Ward; Matthew McKenzie; Anna Bogush; Jacqueline F. Hamilton; Ricardo H.M. Godoi; Ivan Kourtchev (Atmospheric Pollution Research, 2026)

Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Margin of exposure to free formaldehyde in personal care products containing formaldehyde-donor preservatives: Evidence for consumer safety - Sang-Tae Kim; Kan Shao; Christine Oleschkewitz; Ryan Hamilton (Regulatory Toxicology and Pharmacology, 2023)

From green to orange: The change in biochemical composition of phototrophic-mixotrophic Chromochloris zofingiensis in pilot-scale photobioreactors - Eleanor E. Wood; Michael E. Ross; Sébastien Jubeau; Valéria Montalescot; Karen MacKechnie; Ryan E. Marchington; Matthew P. Davey; Sharon McNeill; Callum Hamilton; Michele S. Stanley (Algal Research, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Evidence for ecotone speciation across an African rainforest‐savanna gradient - Adam H. Freedman; Ryan J. Harrigan; Ying Zhen; Alison M. Hamilton; Thomas B. Smith (Molecular Ecology, 2023)
Accelerating climate change and habitat loss make it imperative that plans to conserve biodiversity consider species' ability to adapt to changing environments. However, in biomes where biodiversity is highest, the evolutionary mechanisms responsible for generating adaptative variation and, ultimately, new species are frequently poorly understood. African rainforests represent one such biome, as decadal debates continue concerning the mechanisms generating African rainforest biodiversity. These debates hinge on the relative importance of geographic isolation versus divergent natural selection across environmental gradients. Hindering progress is a lack of robust tests of these competing hypotheses. Because African rainforests are severely at‐risk due to climate change and other anthropogenic activities, addressing this long‐standing debate is critical for making informed conservation decisions. We use demographic inference and allele frequency‐environment relationships to investigate mechanisms of diversification in an African rainforest skink, Trachylepis affinis , a species inhabiting the gradient between rainforest and rainforest‐savanna mosaic (ecotone). We provide compelling evidence of ecotone speciation, in which gene flow has all but ceased between rainforest and ecotone populations, at a level consistent with infrequent hybridization between sister species. Parallel patterns of genomic, morphological, and physiological divergence across this environmental gradient and pronounced allele frequency‐environment correlation indicate speciation is mostly probably driven by ecological divergence, supporting a central role for divergent natural selection. Our results provide strong evidence for the importance of ecological gradients in African rainforest speciation and inform conservation strategies that preserve the processes that produce and maintain biodiversity.

The absence of genotoxicity of Aloe vera beverages: A review of the literature - Sang-Tae Kim; Peter Pressman; Roger Clemens; Allison Moore; Ryan Hamilton; A. Wallace Hayes (Food and Chemical Toxicology, 2023)

Quantifying Cardiothoracic Variation with Posture and Respiration to Inform Cardiac Device Design - Geeth A. Kondaveeti; Varun A. Bhatia; Ryan P. Lahm; Megan L. Harris; James P. Gaewsky; F. Scott Gayzik; John F. Greenhalgh; Craig A. Hamilton; R. Brandon Stacey; Ashley A. Weaver (Cardiovascular Engineering and Technology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Motor unit action potential amplitude during low torque fatiguing contractions versus high torque non-fatiguing contractions: a multilevel analysis - Kylie K. Harmon; Adam S. Hamilton; Brent D. Johnson; Frank J. Bartek; Ryan M. Girts; Rob J. MacLennan; Debbie L. Hahs-Vaughn; Matt S. Stock (European Journal of Applied Physiology, 2021)

Correction to: Redox Modulation at Work: Natural Phytoprotective Polysulfanes From Alliums Based on Redox-Active Sulfur - Awais Anwar; Emma Gould; Ryan Tinson; Javaid Iqbal; Chris Hamilton (Current Pharmacology Reports, 2019)

Development of community of practice to support quantitative risk assessment for synthetic biology products: contaminant bioremediation and invasive carp control as cases - Benjamin D. Trump; Christy Foran; Taylor Rycroft; Matthew D. Wood; Nirzwan Bandolin; Mariana Cains; Timothy Cary; Fiona Crocker; Nicholas A. Friedenberg; Patrick Gurian; Kerry Hamilton; Jan Jeffrey Hoover; et al. (Environment Systems and Decisions, 2018)

Redox Modulation at Work: Natural Phytoprotective Polysulfanes From Alliums Based on Redox-Active Sulfur - Awais Anwar; Emma Gould; Ryan Tinson; Javaid Iqbal; Chris Hamilton (Current Pharmacology Reports, 2018)
Purpose of review This article provides a brief overview of natural phytoprotective products of allium with a special focus on the therapeutic potential of diallyl polysulfanes from garlic, their molecular targets and their fate in the living organisms. A comprehensive overview of antimicrobial and anticancer properties of published literature is presented for the reader to understand the effective concentrations of polysulfanes and their sensitivity towards different human pathogenic microbes, fungi, and cancer cell lines. Recent findings The article finds polysulfanes potentials as new generation novel antibiotics and chemo preventive agent. The effective dose rates of polysulfanes for antimicrobial properties are in the range of 0.5–40 mg/L and for anticancer 20–100 μM. The molecular targets for these redox modulators are mainly cellular thiols as well as inhibition and/or activation of certain cellular proteins in cancer cell lines. Summary Antimicrobial and anticancer activities of polysulfanes published in the literature indicate that with further development, they could be promising candidates for cancer prevention due to their selectivity towards abnormal cells.

Using hospital medical record data to assess the accuracy of the SEER Los Angeles Cancer Surveillance Program for initial treatment of prostate cancer: a small pilot study - Ryan D. Kraus; Ann S. Hamilton; Mari Carlos; Leslie K. Ballas (Cancer Causes & Control, 2018)

Diel behavior in moths and butterflies: a synthesis of data illuminates the evolution of temporal activity - Akito Y. Kawahara; David Plotkin; Chris A. Hamilton; Harlan Gough; Ryan St Laurent; Hannah L. Owens; Nicholas T. Homziak; Jesse R. Barber (Organisms Diversity & Evolution, 2018)

Schema vs. primitive perceptual grouping: the relative weighting of sequential vs. spatial cues during an auditory grouping task in frogs - Hamilton E. Farris; Michael J. Ryan (Journal of Comparative Physiology A, 2017)

Do frog-eating bats perceptually bind the complex components of frog calls? - Patricia L. Jones; Hamilton E. Farris; Michael J. Ryan; Rachel A. Page (Journal of Comparative Physiology A, 2013)

Conserved regulatory motifs at phenylethanolamine N-methyltransferase (PNMT) are disrupted by common functional genetic variation: an integrated computational/experimental approach - Juan L. Rodríguez-Flores; Kuixing Zhang; Sun Woo Kang; Gen Wen; Sajalendu Ghosh; Ryan S. Friese; Sushil K. Mahata; Shankar Subramaniam; Bruce A. Hamilton; Daniel T. O’Connor (Mammalian Genome, 2010)

Phytoplankton assemblages in North Island lakes of New Zealand: Is trophic state, mixing, or light climate more important? - E.F. Ryan; I.C. Duggan; D.P. Hamilton; D.F. Burger (New Zealand Journal of Marine and Freshwater Research, 2006)
Relationships between phytoplankton assemblages and lake trophic state, mixing regime and light climate were investigated in 40 North Island, New Zealand, lakes. We tested the hypothesis that mixing regime is more important than trophic state or light climate in determining the community composition of phytoplankton assemblages which were represented as presence/ absence of cyanobacteria and diatom genera. Mixing regime, characterised as a function of lake size, more accurately predicted summer phytoplankton composition than indices related to trophic state or light regime. Analysis of similarities indicated distinct differences in phytoplankton assemblages between mixed lakes and those that intermittently or periodically stratify. In mixed lakes, a greater variety of cyanobacteria genera than diatom genera were recorded compared with lakes that stratify stably in summer. Conversely, relatively high numbers of diatom to cyanobacteria genera were found in lakes that stratify compared with mixed lakes. Lakes with different trophic states but similar mixing regimes shared very similar summer phytoplankton assemblages. None of the three variables tested was a good predictor of winter phytoplankton composition. Although phytoplankton biomass may be regulated to a large extent by nutrient status, this study shows that mixing regime plays a more important role in regulating phytoplankton composition than either nutrient status or light climate.

Recent occurrence of Cylindrospermopsis raciborskii in Waikato lakes of New Zealand - E. F. Ryan; D. P. Hamilton; G. E. Barnes (New Zealand Journal of Marine and Freshwater Research, 2003)
Cylindrospermopsis raciborskii is a toxin‐producing species of cyanobacteria that in autumn 2003 was recorded for the first time in three shallow (max. depth ≤5 m) Waikato lakes and a hydro‐electric dam on the Waikato River, New Zealand. It formed water blooms at densities >100 000 cells/ml in Lakes Waahi and Whangape. Net rates of population growth >0.2 day –1 were recorded for C. raciborskii in Lakes Ngaroto, Waahi, and Karapiro, based on comparisons of low numbers (detection of 15 000 cells/ml) in the subsequent sample “x”‐“y” days later. C. raciborskii may be well adapted to rapid proliferation in the Waikato lakes, which are eutrophic to hypertrophic, with high light attenuation, and where nitrogen (N) fixation may provide it with a competitive advantage over non‐nitrogen fixing algae under N‐limited conditions.